2015
DOI: 10.1111/ced.12571
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent duplication mutation inHRAScausing mild Costello syndrome in a Chinese patient

Abstract: Costello syndrome (CS; OMIM 218040) is caused by heterozygous germline mutations of HRAS (OMIM 190020).We report on a patient with sporadic CS presenting with characteristic craniofacial dysmorphism, congenital cardiopulmonary disorders, intellectual impairment, and skin abnormalities manifesting as loose redundant skin of the hands and feet, acanthosis nigricans, multiple naevi and hypotrichosis. Using Sanger sequencing for the case-parents trio, we detected a de novo insertion mutation (c.187_207dup) in HRAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Among the less common mutations, HRAS p.E63_D69dup causes an attenuated phenotype with milder intellectual disability, fewer feeding issues, and a lower tumor risk (Lorenz et al, ; Xu, Wang, Lin, & Yu, ). Facial features tend to be less coarse in individuals with the rarer HRAS missense mutations p.T58I, p.K117R, p.A146V, and p.A146P (Chiu et al, ; Gripp et al, ; Kerr et al, ).…”
Section: Mutations and Genotype–phenotype Correlationssupporting
confidence: 91%
“…Among the less common mutations, HRAS p.E63_D69dup causes an attenuated phenotype with milder intellectual disability, fewer feeding issues, and a lower tumor risk (Lorenz et al, ; Xu, Wang, Lin, & Yu, ). Facial features tend to be less coarse in individuals with the rarer HRAS missense mutations p.T58I, p.K117R, p.A146V, and p.A146P (Chiu et al, ; Gripp et al, ; Kerr et al, ).…”
Section: Mutations and Genotype–phenotype Correlationssupporting
confidence: 91%
“…7A). One insertion is reported for two independent cases of Costello syndrome 23,24 and 6 different insertions are reported for 8 tumour samples 2530 . Though these variants are similar to the VMOS RAS variants, it is possible that they have acquired a stronger signalling capability.…”
Section: Resultsmentioning
confidence: 99%
“…( A ) Sequence alignment as in Fig. 2A of a KRAS variant found in a Noonan patient (case 7; this study), a HRAS variant found in two patients with Costello (lit 1; 23,24 ) and of 6 variants of either KRAS or NRAS found in 8 different tumour samples (lit 2–7; 2530 ). The number of independent observations of the variant and the context is indicated on the right of the alignment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activating mutations in the amino acid residues 12, 13, or 61 resulted in elevated levels of GTP‐bound RAS due to the impaired basal GAP‐stimulated hydrolysis of GTP. Recently, intragenic duplications of RAS have been identified in patients with CS or cancers (Gremer et al, 2010; Gripp et al, 2020; Lorenz et al, 2013; Xu et al, 2015). The reported intragenic duplications are located in the switch I region (p.(Glu37dup)) and the switch II region (p.(Glu63_Asp69dup) or p.(Glu62_Arg68dup)).…”
Section: Introductionmentioning
confidence: 99%